The "Old Testaments" of the peoples. Grundtvig's discernment of life's true order (human first, Christian next) and its relevance for the new eco‐recognition of ancestral bonds in time and space. Issue 2 (8th June 2021) - Salomonsen, Jone
Abstract: The intellectual distinction between Jews and Gentiles, Christians and Pagans is a division between true and false religion. Danish theologian N. F. S. Grundtvig (1783–1872) refuted this binary when he "matchlessly discovered" that pagan simply denotes a natural, pre‐Christian human, created in the image of God. Inborn and cultured spirits of life simply convey a people's "Old Testament, " which may also be treasured as independent sources of pride, cultural knowledge, community, and historicity. In this article, I approach Grundtvig's discovery as method, and discuss its potential to teach a climate sensitive age kinship with a particular linage of dwellers (nomads, peasants, Sami, Vikings, moderns), a specific landscape, and with spirit as breath and sensory belonging to a larger‐than‐human community. It will include a brief reflection on how native Christian scholars treat this problematic, how gendered rereadings of Norse mythology may still enlighten the present, and how new ecological concerns about deep entanglements may open Norwegian memory to its first migrants: nomadic hunters and gatherers.